Effect of carbon/nitrogen ratio and ferric ion on the production of biohydrogen from palm oil mill effluent (POME). (January 2020) - Abdullah, Mohamad Farizzuan; Md Jahim, Jamaliah; Abdul, Peer Mohamed; Mahmod, Safa Senan
Abstract: Palm oil mill effluent (POME), the liquid discharge of palm oil milling process, is rich in organic carbon, nitrogen, and minerals. Over the years, dark fermentation has been chosen to treat POME and to generate biohydrogen. This study was conducted to further improve this process by evaluating the effect of the nitrogen to carbon (C/N) ratio and concentration of ferric ion (Fe 2+ ) on biohydrogen by using a thermophilic mixed culture. A synthetic media consisting of glucose and xylose as main carbon source was used to determine the effect of nutrient adjustment on POME at temperature and pH of 55 °C and 6.0, respectively. The inorganic nitrogen sources were determined by using three different nitrogen sources, namely; ammonium nitrate, ammonium chloride and ammonium sulfate. Addition of ammonium nitrate resulted in biohydrogen yield of 1.65 molH₂ /molsugar, whereas the other two salts showed inhibitory effects on the fermentation process. Furthermore, biohydrogen production was increased by 28% and 15.53% at C/N ratio of 140 and Fe 2+ concentration of 100 mg/L, respectively. The optimum parameters obtained in this study were validated using POME as fermentation medium, and resulted in biohydrogen yield of 1.88 molH₂ /molsugar . The results suggested that the addition of nutrients, Fe 2+ and nitrogen source are vital factors to improve the biohydrogen productivity significantly. Highlights: Synthetic media was used as a model for POME in the fermentation study. Three different sources of nitrogen were tested on biohydrogen productivity. The fermentation process has been subjected to the C/N ratio and ferric ion concentration variations. Fermentation of POME resulted in biohydrogen yield of 1.88 molH₂ /molsugar .